Route Choice Analysis to Office Areas Using “All or Nothing” Approach and User Perceptions - Gilang Farhanudin; Nursuci Mar’atussolicha; Siti Aisyah Agustin; Mira Lestari Hariani (International Journal Labs, 2025)
Route selection is a critical process in designing an efficient transportation system, as inaccuracies in route choice can lead to delays and adverse effects on worker health and productivity. The purpose of this study is to identify preferences and factors influencing the selection of travel routes, as well as to map alternative routes based on these influential factors. The methods employed in this study include a questionnaire survey of office workers, which was then analyzed using the ordinal logit model and multinomial logistic regression with the assistance of SPSS software. Additionally, the all-or-nothing assignment method was applied to determine the optimal routes, using ArcGIS as a geospatial mapping and analysis tool. The results indicated that traffic density, distance, travel cost, and travel time were the primary factors affecting route choice decisions, with cost being the most significant. Conversely, individual characteristics such as age, gender, and education level did not have a statistically significant effect. This study recommends the adoption of an alternative route selection model to identify the most efficient commuting routes from various zones within the region, considering key factors such as traffic congestion levels, distance, cost, and travel time efficiency.